2021
DOI: 10.1186/s12995-021-00322-2
|View full text |Cite
|
Sign up to set email alerts
|

Online survey among maritime pilots: job-related stress and strain and the effects on their work ability

Abstract: Background Maritime pilots often navigate ships through challenging waterways. The required 24 h standby rotation system (ROS) poses a stressful working situation. This study aims to describe the current job-related stress and strain among maritime pilots and the effects on their work ability, taking into account the different rotation systems. Methods Within a cross-sectional survey, pilots of all German pilots’ associations were asked to complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Their review identified a number of wellbeing and health-related issues, such as long shifts, challenging tasks, commercial pressures and irregular, unpredictable and unsocial working hours, which often led to stress, fatigue and family conflict. A recent survey of German pilots [35] confirmed these findings. It also found that about 20% of the respondents had experienced at least one accident involving personal injury and that more than half of them had experienced at least one accident involving damage to a vessel [35] .…”
Section: Literature Reviewmentioning
confidence: 59%
See 3 more Smart Citations
“…Their review identified a number of wellbeing and health-related issues, such as long shifts, challenging tasks, commercial pressures and irregular, unpredictable and unsocial working hours, which often led to stress, fatigue and family conflict. A recent survey of German pilots [35] confirmed these findings. It also found that about 20% of the respondents had experienced at least one accident involving personal injury and that more than half of them had experienced at least one accident involving damage to a vessel [35] .…”
Section: Literature Reviewmentioning
confidence: 59%
“…A recent survey of German pilots [35] confirmed these findings. It also found that about 20% of the respondents had experienced at least one accident involving personal injury and that more than half of them had experienced at least one accident involving damage to a vessel [35] . This suggests that pilotage accidents may be common.…”
Section: Literature Reviewmentioning
confidence: 59%
See 2 more Smart Citations
“…Hence, by having ineffective MIS in the organization, it could contribute to many disadvantages especially in maritime industry. This can be supported by Oldenburg et al, [24], which stated that Maritime pilots need 24 hours to standby in order to navigate ships, thus lead to very stressful working situation. As maritime pilots are key stakeholders in maritime industry, it will give many advantages to them if there is effective management by using MIS [2].…”
Section: 1 Management Information System (Mis) Functionalitymentioning
confidence: 95%